Analysis of Time Commitment and Performance of Management Towards Patient Services in The Karanggeneng Lamongan Sahabat Health Clinic - Evi Fitrotun Najiah (Jurnal Mantik, 2020)
This study aims to determine the time commitment and management performance in order to test its effect on clinic patients' health care services with hypotheses presumed that there are partial or simultaneous influences between variables X1, X2 and Y and predictable management performance variables X2. This type of research is descriptive statistics with an approach Quantitative testing of 100 respondents using a questionnaire distributed to the climax of healthy friends. besides, done by interview method The results of the study show that there is a positive influence of time commitment variable (X1) and management performance (X2) in influencing patient service with the results of the regression equation Y = 1,198 + 0,268 X1 + 0,668X2 It can be concluded that time commitment variables and management performance partially influences the commitment of time and management performance partially affecting the service of clinical patients healthy friends because of lamogan, this is evidenced by the regression coefficient of 0.668 or 66.8% and the tcount for management performance (X2) that is equal to tcount> ttable which is 1,463> 1,984.